Synthetic biology for microbial production of lipid-based biofuels. (December 2015) - d'Espaux, Leo; Mendez-Perez, Daniel; Li, Rachel; Keasling, Jay D
Highlights: Biological lipids are naturally energy-dense and several make good biofuels. Metabolic pathways to produce these biofuels have been engineered in microbial hosts. A wide range of tools and methodologies are available for improving biofuel production. Synthetic biology offers great potential for sustainable manufacturing. Abstract : The risks of maintaining current CO2 emission trends have led to interest in producing biofuels using engineered microbes. Microbial biofuels reduce emissions because CO2 produced by fuel combustion is offset by CO2 captured by growing biomass, which is later used as feedstock for biofuel fermentation. Hydrocarbons found in petroleum fuels share striking similarity with biological lipids. Here we review synthetic metabolic pathways based on fatty acid and isoprenoid metabolism to produce alkanes and other molecules suitable as biofuels. We further discuss engineering strategies to optimize engineered biosynthetic routes, as well as the potential of synthetic biology for sustainable manufacturing.